The Effects of Extended Release Niacin on Lipoprotein Sub-Particle Concentrations in HIV-Infected Patients - Lin, Chunrong (University Clinical, Education & Research Associate (UCERA), 2013)
INTRODUCTION: With the advent of highly active antiretroviral therapy (HAART), Cardiovascular Disease (CVD) has emerged as the leading cause of death in Human Immunodeficiency Virus (HIV) infected patients. An atherogenic lipoprotein phenotype has been described in HIV-infected patients with a predominance of small, dense LDL (SLDL) particles with accompanying elevated triglycerides and reduced high density lipoprotein cholesterol. This randomized controlled pilot study was conducted to evaluate the efficacy of Extended Release Niacin (ERN) in reversing the atherogenic lipoprotein phenotype. METHODS: A total of 17 HIV positive subjects on HAART therapy with High Density Lipoprotein Cholesterol (HDL-c) levels below 40mg/dl and Low Density Lipoprotein Cholesterol (LDL-c) below 130mg/dl were enrolled. Nine were randomized to be treated with ERN titrated from a starting level of 500mg/night and titrated to a level of 1500mg/night. Eight patients were assigned to the control arm. No placebo was used. Lipoprotein profiles of the subjects were analyzed at baseline and at the end of 12 weeks with Nuclear Magnetic Resonance (NMR) spectroscopy. Results At the end of 12 weeks, NMR spectroscopic analysis revealed a significant increase in overall LDL size (1.22% in ER Niacin treated subjects vs −1.96% in control patients, P= .04) and a decrease in small LDL particle concentration (−17.02% in ERN treated subjects vs 21.42% in control patients, P = .03) in subjects receiving ERN as compared to those in the control group. Only 1 subject receiving ERN developed serious flushing which was attributed to an accidental overdose of the drug. CONCLUSIONS: This pilot study demonstrates that ERN therapy in HIV-infected patients with low HDL-c is safe and effective in improving the lipoprotein profile in these patients.